Electric Motor Drives. Modeling, Analysis, and Control - Krishnan R. (New Jersey, Prentice Hall, 2001)
Electric Motor Drives is a comprehensive book for seniors, graduates, and practicing engineers. Designed to motivate students and professional engineers alike, the book emphasizes a systematic approach to motor drives based on physical insight and practical implementation aspects. DC and AC drives share the same pedagogical framework throughout. Present day practice as well as recent research and development are covered.